2023
DOI: 10.1039/d3ra04321e
|View full text |Cite
|
Sign up to set email alerts
|

Injectable fillers: current status, physicochemical properties, function mechanism, and perspectives

Abstract: Injectable fillers have great potential in the correction of facial wrinkles and lines. The longevity of injectable fillers varies from 1 month to 5 years based on the physicochemical properties, fabrication strategy, and function mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…As one of the most commonly used body soft tissue fillers, HA not only plays a filling role but also stimulates the production of skin collagen fibers and various growth factors [18][19][20]. In this study, we demonstrated the efficacy of ultrasound in assessing the filling properties of HA fillers in vivo and found that it could capture uplift data after filling and produce fine-grained data.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As one of the most commonly used body soft tissue fillers, HA not only plays a filling role but also stimulates the production of skin collagen fibers and various growth factors [18][19][20]. In this study, we demonstrated the efficacy of ultrasound in assessing the filling properties of HA fillers in vivo and found that it could capture uplift data after filling and produce fine-grained data.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, ultrasound measurement can obtain finer uplift data after filling and can compensate for the shortcomings of the subjective factors in vernier caliper measurement, which leads to large deviations. The source of HA, degree of crosslinking, and differences in the composition of different products affect the duration of the filling effectiveness of the products [19]. Therefore, an ideal animal model and test can provide quantifiable data and indicators for materials research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Injectable dermal fillers, ranking as the second most common non-invasive aesthetic procedure, are increasingly utilized for soft tissue augmentation and rejuvenation [ 115 ]. These fillers serve to restore volume to skin depressions, thereby contributing to a youthful and rejuvenated appearance [ 116 ].…”
Section: Reviewmentioning
confidence: 99%
“…These fillers serve to restore volume to skin depressions, thereby contributing to a youthful and rejuvenated appearance [ 116 ]. The market currently offers a growing variety of these fillers, with common biodegradable examples including hyaluronic acid, calcium hydroxylapatite, poly-L-lactic acid, and dextran beads in hyaluronic acid [ 115 , 116 ]. While the primary mechanism of action of dermal fillers is to provide sufficient physical volume to compensate for loss, there is also evidence suggesting that these fillers are not inert.…”
Section: Reviewmentioning
confidence: 99%
“…Injectable hydrogels intended for soft-tissue augmentation must exhibit analogous mechanical properties to those of the target tissues and degrade slowly to maintain volume in vivo. Rather than merely occupying space, these hydrogels interact with host cells to perform functions, like promoting subcutaneous cell proliferation, collagen deposition, and tissue regeneration [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%